Biosynthesis, structure and functionality of starch granules in maize inbred lines with different kernel dehydration rate. (30th January 2022) - Qu, Jianzhou; Zhong, Yuyue; Ding, Li; Liu, Xingxun; Xu, Shutu; Guo, Dongwei; Blennow, Andreas; Xue, Jiquan
Highlights: Relationships between maize dehydration rate and starch structure were disclosed. Dehydration rate was correlated with the expression of starch synthesis related genes. Maize with fast kernel dehydration rate had amylose with low molecular size. Maize with fast dehydration rate had low content of amylopectin chains of DP6-12. Maize with fast kernel dehydration rate had high retrogradation rate. Abstract: In this study, we report important relationships between kernel starch and kernel dehydration rate for eight maize inbred lines with different dehydration characteristics. High-throughput RNA sequencing data of starch biosynthesis-related genes showed that kernel moisture content and dehydration rate were both associated with differential expression of most starch biosynthetic genes. Especially, kernel moisture content was positively correlated with the increased expression of SBEI and SBEIIb, thereby potentially inducing biosynthesis of amylose with low molecular weight and amylopectin with low content of amylopectin chains with degree of polymerization (DP) 6-12 in inbred lines with fast kernel dehydration rate. We found a negative correlation between short amylopectin chains (DP 6-12) and the starch retrogradation rate. Hence, a low amount of amylopectin chains with DP 6-12 in the inbred lines with fast kernel dehydration rate was a plausible reason for their high short- and long-term retrogradation.